Ozonation in Wastewater Disinfection - Zamorska, Justyna; Kiełb-Sotkiewicz, Izabela (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Due to the potential microbiological hazard associated with discharging treated sewage into the receiving body, its disinfection is a key issue to protect ecological safety and human health. Water scarcity and drinking water supply, irrigation, rapid industrialization, use of treated water, protection of water sources, overpopulation and environmental protection force us to look for solutions to ensure safe reuse of wastewater, and this depends primarily on the quality of wastewater disinfection.
Keywords: municipal wastewater; disinfection; ozonation; ATP; FCM